The Role of Community Participation Toward Economic Empowerment in the Tourism Sector - Cahyaningrum, Dinis; Hasani, Tifani Dame; Asri, Ni Wayan Adelia Mutiara; Safitri, Dhanny; Ibrahim, Isra Dewi Kuntary (West Science Business and Management, 2024)
This study examines the relationship between community participation and economic empowerment in the tourism sector using a qualitative descriptive approach and literature review. The main focus of this research is to highlight the importance of community participation at various stages of tourism development, from planning to evaluation. Community participation is crucial as it not only enhances the sense of ownership over tourism projects but also creates new job opportunities and acts as diverse sources of income for the community. By involving communities in providing tourism services—such as guiding, handicrafts, and local cuisine—they can contribute directly to the industry while preserving and promoting local wisdom. Training programs conducted for communities aim to enhance their capacity and skills, enabling them to adapt to the ever-evolving dynamics of the tourism market. Furthermore, strengthening the cultural identity of communities by introducing local values is a vital aspect of attracting tourist interest. The findings of the study indicate that active community participation positively impacts individual well-being and contributes to sustainable economic development, ensuring the benefits of tourism are distributed equally among all involved communities. This research highlights that empowering communities through active engagement at all stages of tourism development fosters resilience, supports cultural preservation, and promotes equitable economic growth, offering a sustainable model for community-based tourism initiatives.